2013
DOI: 10.3354/cr01166
|View full text |Cite
|
Sign up to set email alerts
|

Hydroclimatology of the Southeastern USA

Abstract: We provide an overview of the hydroclimatology of the Southeastern USA, and review the primary factors that influence hydroclimatic variability on seasonal to interannual timescales. The Southeastern USA is characterized by high mean annual precipitation, but with significant variability. Precipitation variability is on the rise in this region, with more frequent, longer duration dry periods and infrequent, short duration, but heavy precipitation events. Hydroclimatic extremes are a relatively common occurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 104 publications
(192 reference statements)
0
17
0
Order By: Relevance
“…Additionally, teleconnection patterns likely influence hydroclimatic trends differently in the SAM than in the SEUS due to the added influence of topographic variability and its interaction with the low level moisture flux from the surface to the middle troposphere. Very few stations have significant correlations between these teleconnection patterns and heavy precipitation variability, whereas these teleconnection patterns are known to have a marked influence of hydroclimatic variability in the SEUS [13,17,[20][21][22][23].…”
Section: Warm Season Event Counts and Climate Index Correlationmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, teleconnection patterns likely influence hydroclimatic trends differently in the SAM than in the SEUS due to the added influence of topographic variability and its interaction with the low level moisture flux from the surface to the middle troposphere. Very few stations have significant correlations between these teleconnection patterns and heavy precipitation variability, whereas these teleconnection patterns are known to have a marked influence of hydroclimatic variability in the SEUS [13,17,[20][21][22][23].…”
Section: Warm Season Event Counts and Climate Index Correlationmentioning
confidence: 99%
“…Topographic and geographic features, such as slope, aspect, elevation, and exposure are known to play critical roles in the spatial distribution of precipitation events, thus adding regional differences within the SEUS [7,8]. The hydroclimate of the SEUS is changing, with increased precipitation variability and dry spells [2,6,[11][12][13][14]. Many changes have occurred during the warm season.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrologic variability in the SEUS in terms of precipitation and streamflow can be partly explained by the phase of various hydroclimatological teleconnections (Kahya and Dracup, 1993;Labosier and Quiring, 2013;Engström and Waylen, 2017a). Previously, Labosier and Quiring (2013) reviewed the hydroclimatology of the e1140 V. SEHGAL AND V. SRIDHAR SEUS and concluded that the region is strongly impacted by El Niño-Southern Oscillation (ENSO), the Pacific North American (PNA) pattern, the Bermuda High, and tropical cyclones. ENSO, the North Atlantic Oscillation (NAO), and PNA pattern all found to significantly change seasonal precipitation and run-off in the SEUS (Engström and Waylen, 2017a).…”
Section: Introductionmentioning
confidence: 99%